Răspuns :
Răspuns:
Explicație pas cu pas:
3^(x-1) + 3^(x-2) + 3^(x-3) + 3^(x-4) + 3^(x-5) + 3^(x-6) = 364
3^(x-6)(3^5 + 3^4 + 3^3 + 3^2 + 3 + 1) = 364
3^(x-6)(243 + 81 + 27 + 9 + 3 + 1) = 364
364*3^(x-6) = 364
3^(x-6) = 364 : 364 = 1
x - 6 = 0
x = 6
Raspuns:
[tex]3 {}^{x - 1} + 3 {}^{x - 2} + 3 {}^{x - 3} + 3 {}^{x - 4} + 3 {}^{x - 5} + 3 {}^{x - 6} = 364[/tex]
[tex](3 {}^{5} + {3}^{4} + {3}^{3} + {3}^{2} + 3 + 1) \times 3 {}^{x -6 } = 364[/tex]
[tex](243 + 81 + 27 + 9 + 3 + 1) \times 3 {}^{x - 6} = 364[/tex]
[tex]364 \times 3 {}^{x - 6} = 364[/tex]
[tex]3 {}^{x - 6} = 1[/tex]
[tex] {3}^{x - 6} = 3 {}^{0} [/tex]
[tex]x - 6 = 0[/tex]
[tex]x = 6[/tex]
Explicație pas cu pas: